Count Alerino Palma in the Age of Revolutions or Greek 1821 in Context - Maria Christina Chatziioannou (Diasporas: Circulations, Migrations, Histoire)
The story of an Italian political migrant, Count Alerino Palma, elucidates key elements of the revolutionary 1820s when former Napoleonic officers served various democratic uprisings around the Mediterrannean. Palma finally offered his expertise in the case of the first Greek loan and the juridical system of the new‑born Greek state, where he finally established himself. Through his geographic wanderings and new experiences, Palma transformed his democratic political ideas sustaining constitutional monarchy. His case study of the Greek‑Italian “political friendship”, marks a transitional period which fuelled the 1820s transnationalism at the dawn of the nation-state era of many Mediterranean countries.